Local Innovation Systems and Benchmarking - Uwe Cantner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper reviews approaches used for evaluating the performance of local or regional innovation systems. This evaluation is performed by a benchmarking approach in which a frontier production function can be determined, based on a knowledge production function relating innovation inputs and innovation outputs. In analyses on the regional level and especially when acknowledging regional innovation systems those approaches have to take into account cooperative invention and innovation the core of the innovation system approach. To make these interactive effects visible, a method is suggested to identify the relative regional impact on cooperative innovative activities.
Keywords: O3; R11; C2; C6; 330; Benchmarking; regional innovation systems; frontier function approaches; Innovation; Business Network; Forschungskooperation; Region; Benchmarking; Wissen; Technische Effizienz; Schätzung; Deutschland